STUDENTS DIFFICULTIES IN TRANSLATING CULTURE-SPECIFIC TERMS - Jepri Jepri (Prologue: Journal on Language and Literature, 2017)
This research is the study of the difficulties faced by students of semester V faculty of Letters, Balikpapan University in translating a culture-specifictext from English to Indonesian Language. The research is qualitative; datacollecting is done by distributing the text contains American culture ofbaseball sports to translate and interviewing students to identify theirdifficulties. From the result, it is concluded that the difficulties faced bystudents in translating the texts is caused by their lack of understanding ofthe Source Language culture, in this case , the baseball sports, their poorknowledge of the sport itself and their low experience in reading adiscourse from the same context. It is recommended for translation subjectlecturer to provide students a broad knowledge of the cultural context ofsource language to help them improve their translation skills.